Effects of Cd and Zn Treatments on Leaf Chemıcal Compounds of Japanese barberry (Berberis thunbergii), Boxwood (Buxus sempervirens var. rotundifolia), and Gold tassel (Euonymus japonica var. aurea) Species - GENÇ, Erkan; TURFAN, Nezahat (Igdir University, 2023)
In the present study, the effects of cadmium (25 μM and 50 μM) and zinc (200 μM and 400 μM) treatments on some bioactive compounds and mineral levels in leaves of japanese barberry, boxwood, and gold tassel genotypes were investigated. Given the results, it was determined that photosynthetic pigments were stimulated by 200 μM Zn and 400 μM Zn. Boxwood was found to be tolerant to the treatments in terms of chlorophyll and carotenoid. In contrast, japanese barberry was found to be tolerant in terms of chlorophyll b and total chlorophyll. The amount of anthocyanin was higher in the leaves of gold tassel, and boxwood and the total phenolic was higher level in gold tassel and japanese barberry in all treatments. Proline and nitrate levels were generally high in the treated groups of three plants, as well as RWC in japanese barberry and boxwood. Given the element results, japanese barberry had a higher accumulation capacity for P, S, Mn, Cl, Cd, Fe, Al, Si, Cu, Ba, Zn, Ti, and Cr, boxwood for K, Mn, Cl, Cd, Zn, Fe, Al, Si, and Cr, and Gold tassel for K, P, S, Mn, Cl, and Cd. As a result, boxwood showed a higher tolerance to 400 μM Zn, japanese barberry plant to 200 μM Zn, and 50 μM Cd. It can be said that boxwood and japanese barberry plants can be used in afforestation projects in urban parks, gardens, and roadside, as well as in areas with high soil pollution, to reduce the pollution damage.
Keywords: Chemicals; Metals; Nutrient; Plants; Stress; Structural Biology; Yapısal Biyoloji; 13. Climate action; 11. Sustainability; 6. Clean water